Fabrication of the Colored PMIA Fibers by Wet Spinning: Effect of Spinning Parameters on the Coagulation Process. Issue 1 (March 2014) - Liu, Liqi; Chen, Lei; Hu, Zuming; Yu, Junrong; Jing-Zhu,; Sun, Jinliang; Ren, Musu
The poly (m-phenylene isophthalamide) (PMIA) fiber, which can be prepared by wet spinning, is a kind of aromatic polyamide fiber. The spinning parameters could influence the performance and structure of the colored PMIA fiber such as the diffusion coefficient and coagulation bath. In this study, the PMIA spinning solutions doped with Color Inde purple 120 were first commixed in a pressurizer and then spun into a coagulation bath under a pressure about 0.3 MPa. In the coagulation bath, the pure or dope-dyed PMIA fibers were prepared by wet spinning at 323 K, and then the as-spun fibers were extracted by an ultrasonic oscillation method. The effects of jet stretch ratio, temperature, and concentration of the coagulation bath on the ratio of diffusion coefficient of solvent to coagulator were analyzed during the spinning process of dope-dyed PMIA fibers. The properties and structures of the colored PMIA fibers were characterized by SEM. Finally the most optimized spinning technology of the dope-dyed PMIA fiber was obtained and the dope-dyed PMIA fibers were successfully fabricated through wet spinning.